Optimizing the implementation of business model canvas in elevating the Garuda Futsal League as a premier sports tourism event - Nusantara, Muhammad Akhva Aulia; Kaihatu, Thomas Stefanus (Bahasa Indonesia, 2025)
This study aims to examine the implementation of the Business Model Canvas (BMC) approach in organizing the Garuda Futsal League (GFL) Series 1 in Surabaya. GFL is an inter-school futsal competition that is designed professionally and innovatively with a focus on developing talented young athletes. Through an implementation method with the BMC theory, GFL has succeeded in creating a structured and professional competition model, by offering a main value proposition, namely improving the quality of performance supported by the use of digital technology in recording player statistics. GFL also presents a sportainment concept that has succeeded in attracting the attention of participants and spectators widely. This study shows that the implementation of the BMC approach is able to create a sustainable student sports competition ecosystem operationally, economically, and socially. Furthermore, by integrating the concept of sports tourism, events like GFL contribute not only to the development of youth sports but also to the promotion of Surabaya as a vibrant destination for sports tourism. As a result, GFL not only provides direct benefits in the form of high-quality futsal competitions but also delivers strong social and economic value, attracting the interest of government and private sectors to become long-term sponsors.